KONSERVASI TRADISIONAL BERBASIS KEARIFAN LOKAL MASYARAKAT TANI KABUPATEN PASER (Studi Kasus Desa Semuntai Kecamatan Long Ikis Kabupaten Paser) - Eko Harri Yulianto (Universitas 17 Agustus 1945 Samarinda, 2013)
Research objectives are : ( 1 ) to determine and assess some local knowledge ( indigenous knowledge ) which is owned by the farmer in the village of Long Ikis Semuntai Paser district on land management in everyday life , and ( 2 ) to assess the modernization paradigm and its impact on conservation traditional communities based on local knowledge .The experiment was conducted for 3 months in the village Semuntai , District Long Ikis , Paser . The stipulation determined purposively based on the consideration that the area is an area where there are many natives who know historically about darts local knowledge ( indigenous knowledge ) in the farming community Paser .This study uses descriptive qualitative approach . Descriptive method is used to describe the facts relevant to the issues under study as it is followed by rational interpretation . Data were collected from two sources , namely : ( 1 ) primary data obtained through in-depth interviewing techniques ( in- depht interviews ) , Focused Group Discussion ( Focus Group Discussion - FGD ) , and observation . While the secondary data obtained from the documents , reports , publications , and so on.Traditional conservation basically is aknowledge system that obtain from human interaction with the environment along all cultural aspects. This system became basis to decision-making and aseducation substabce in traditional community. People of Paser Society (Orang Paser) is community that till recent some of their people remain implementing the traditional conservation, by developing the local wisdom system harmonize with the given culture norms. As the civilization development, this conservation tradition with local wisdom basis suffer degradation bacause of the modernization.